The Use of a Length-Structured Multispecies Model Fitted Directly to Data in Near-Real Time as a Viable Tool for Advice - Spence, Michael A.; Dolder, Paul J.; Nash, Richard; Thorpe, Robert B. (Frontiers in Marine Science, 2021)
Fish communities are multispecies assemblages, so ideally multispecies models should be used directly for assessing this resource. However, progress in this direction has been slow, partly because these models are often more complex and take longer to fit, rendering them too slow to demonstrate near-real-time utility, and thus creating a perception that they are opaque to stakeholders. In this study we implemented a multispecies assessment for the Irish Sea, fitting a model of eight key stocks directly to catch and survey data. Two novel features of our approach allowed the multispecies model to be fitted within a few hours. Firstly, by using size-based theory and life-history invariants to specify many of the required properties of stocks, we reduced the number of parameters that needed to be fitted directly to a more manageable 25. Secondly, by using state-of-the-art fitting methods, we found acceptable solutions quickly enough to provide assessments within the timescale of an advisory meeting. The outcomes were compared with the standard single species assessments of the same species. Model fits to catch and survey data were generally good, though the estimates of natural mortality were not realistic for all stocks. This method shows great promise for making multispecies assessments because of the rapid turnaround time and ability to respond at meetings to the requests of stakeholders. In addition, these models avoid our current dependence on existing single species models, produces length (age) -structured estimates of stock abundance, and are easily accessible because they are based upon freely available code.